The Choreography of Bedhaya Gandakusuma Dance with Mangkunegaran Style: The Study of Movement Patterns - Sriyadi Sriyadi (Jurnal Seni Tari, 2023)
Movement patterns in Javanese dance works are formed from types of movement series constructed to become a unified whole. This series of movements is often called a motion motif, a motion range, or sekaran. A series of movements can be likened to a puzzle arranged in such a way as to form a unified whole. This article aims to describe the movement patterns of the Bedhaya Gandakusuma dance with Mangkunegaran style. This description is essential to know the construction of the movement pattern used. This research is a form of qualitative research with an ethnochoreological approach. Data collection techniques used are participant observation, interviews, and literature study. The results show that the construction of the Bedhaya Gandakusuma dance movement patterns consists of elements of gesture and movement that become the basic material in the arrangement of each series of movements. In the arrangement process, it is tied with a motif or a basic movement as a unifying thread. The basic movement is a series of ngenceng movements. It means that the series of ngenceng movements become the foundation in various variations of the series of movements used. The series of movements are connected by using transition movements (sendhi). The movement patterns construction of the Bedhaya Gandakusuma dance not only considers motifs, variations, and transitions but also considers repetition, climax, proportion, logical development, and unity. The purpose is to achieve wholeness to give vitality in conveying the meaning or essence being expressed.